Catastrophic job destruction - Carneiro, Anabela; Portugal, Pedro; Varejao, José (Paris, 2013)
"In this article we study the resilience of the Portuguese labor market, in terms of job flows, employment and wage developments, in the context of the current recession. We single out the huge contribution of job destruction, especially due to the closing of existing firms, to the dramatic decline of total employment and increase of the unemployment rate. We also document the very large increase in the incidence of minimum wage earners and nominal wage freezes. We explored three different channels that may have amplified the employment response to the great recession: the credit channel, the wage rigidity channel, and the labor market segmentation channel. We uncovered what we believe is convincing evidence that the severity of credit constraints played a significant role in the current job destruction process. Wage rigidity is seen to be associated with lower net job creation and higher failure rates of firms. Finally, labor market segmentation seemed to have favored a stronger job destruction that was facilitated by an increasing number of temporary workers."